PENERAPAN PEMBINAAN INTENSIF DALAM UPAYA PENINGKATAN KINERJA GURU DI MTSN 01 KEPAHIANG - Yusrijal Yusrijal (Jurnal Literasiologi, 2020)
The Action Research “ Implementation of intensive supervision to improve teacher ‘s ability “ inmastering teaching material using strategy,and method of learning, evaluating and discipline.Research method is action resear.researher is helped by this friends from Public Islamic Junior High School 01 Kepahiang. Technical of gathering data is by using observation, interview and documentation. The result of this research show that by implementation of intensive construction to the teacher’s can improve teacher’s ability in mastering materials,using method and strategi avaluative and dicipline in learning.